2003
DOI: 10.2337/diacare.26.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Influences on Insulin Resistance

Abstract: OBJECTIVE -To assess the independent associations of a broad range of early life risk factors and adult obesity with adult insulin resistance.RESEARCH DESIGN AND METHODS -This was a cross-sectional study of 1,394 women, aged 60 -79 years, from 23 British towns.RESULTS -There was a strong (independent of confounding factors, other early life factors, and adult waist-to-hip ratio) inverse association between birth weight and insulin resistance in women in the highest third of BMI (Ͼ28.77 kg/m 2 ): Ϫ0.12 (95% CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1
3

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 39 publications
6
51
1
3
Order By: Relevance
“…7,[35][36][37][38][39] However, when the estimates obtained for each measure of obesity were controlled for potential confounders and for the other obesity measure, the results relative to SBP are less consistent, and in some cases the association disappears. 21,36,37 In our study, as well, the association between body mass index and increased SBP in women and between waist-to-hip ratio and increased SBP in men disappeared after adjusting for the other measures of obesity. Only the association between waist circumference and SBP in women remained after adjusting for all the variables.…”
Section: Pulse Systolic and Diastolic Blood Pressure In Older Peoplesupporting
confidence: 60%
See 1 more Smart Citation
“…7,[35][36][37][38][39] However, when the estimates obtained for each measure of obesity were controlled for potential confounders and for the other obesity measure, the results relative to SBP are less consistent, and in some cases the association disappears. 21,36,37 In our study, as well, the association between body mass index and increased SBP in women and between waist-to-hip ratio and increased SBP in men disappeared after adjusting for the other measures of obesity. Only the association between waist circumference and SBP in women remained after adjusting for all the variables.…”
Section: Pulse Systolic and Diastolic Blood Pressure In Older Peoplesupporting
confidence: 60%
“…Most, 20 but not all, 21,22 studies have observed that impaired foetal development -reflected by low birth weight or other indicators -is associated with increased blood pressure in adulthood. As prenatal growth influences height reached in adulthood, 23 the failure to adjust for some indicator of foetal development could have overestimated the magnitude of the association between height and SBP and underestimated the magnitude of the association between height and DBP.…”
Section: Data Limitationsmentioning
confidence: 99%
“…Assessment of lipids and C-reactive protein was done using standard procedures. 21,22 Full ethics committee approval for the study was obtained from Local Ethics Committees in each of the 23 participating towns and informed consent to review their general practice medical records was obtained from each participant included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…This is suggested by several epidemiological studies describing specific patterns of early growth, such as low weight gain in infancy and rapid gain in BMI during childhood, that aggravate the association between low birth weight and metabolic characteristics and health in later life. 2,4,[38][39][40][41] In a recent study on associations between birth measures and glucose intolerance, we showed that subjects born light or thin benefited specifically from regular exercise. 42 These findings constitute a rationale for future intervention studies, aiming at increasing muscle mass in relation to fat mass, to prevent type 2 diabetes, cardiovascular disease and related traits in individuals at increased risk of these disorders because of their low birth weight.…”
Section: Public Health Implicationsmentioning
confidence: 99%